2017
DOI: 10.21129/nerve.2017.3.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Injury in Adults

Abstract: Brachial plexus injury (BPI) is a severe peripheral nerve injury affecting upper extremities, causing functional damage and physical disability. The most common cause of adult BPI is a traffic accident, and the incidence has steadily increased since the 1980s. BPIs can be divided into three types; preganglionic lesion, postganglionic lesion, and a combination of both. Whether the continuation of the root and the spinal cord is preserved is a critical factor in determining the treatment strategy. The level of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 74 publications
2
44
0
1
Order By: Relevance
“…This matched with [36] who explained in his study that approximately 60% of patients with radial neuropathy at the SG showed CB at the SG . This result also met that by [37] who reported that patients with C8-T1 (lower trunk) lesion showed absent SNAPs from little finger with neurogenic pattern in EDC, EIP, FPL, lumbricals, interossei, thenar and hypothenars while in C5-T1 (panplexopathy) lesion, SNAPs from all fingers were absent with neurogenic pattern in proximal and distal muscles.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This matched with [36] who explained in his study that approximately 60% of patients with radial neuropathy at the SG showed CB at the SG . This result also met that by [37] who reported that patients with C8-T1 (lower trunk) lesion showed absent SNAPs from little finger with neurogenic pattern in EDC, EIP, FPL, lumbricals, interossei, thenar and hypothenars while in C5-T1 (panplexopathy) lesion, SNAPs from all fingers were absent with neurogenic pattern in proximal and distal muscles.…”
Section: Discussionsupporting
confidence: 86%
“…In myelopathy, the clinical clues were old age of patients, gradual onset of radicular paresthesia, weakness and wasting, and late spastic paraparesis with sphincteric disturbances. Electrophysiologically, normal conductions with chronic neurogenic pattern in the lower cervical roots (C7.8 and T1) muscles and degenerative lower cervical myelopathy in the cervical MRI were found and this matched with [30][31][32][33][34][35][36][37][38] who reported that cervical spondolytic myelopathy is the commonest spinal cord disorder in old people with a slow insidious onset of radicular paresthesia followed by fine motor skills dysfunction and atrophy of the hand or shoulder. agreed with [39,40] who reported that symptoms in syringomyelia develop slowly with dissociative paresthesias in a cape or half-cape distribution, and atrophy of intrinsic hand muscles or fasciculations may also be an early finding; signs of myelopathy in lower limbs can become evident as the disease progresses.…”
Section: Discussionmentioning
confidence: 65%
“…Magnetic resonance imaging signal changes are known to occur in the spinal cord in about 20% of cases with brachial plexus injury resulting from edema in the acute phase, and transforming into irreversible myelomalacia in the chronic phase. 25 However, the reversal of the CNS changes in our cases on follow-up without the development of myelomalacia may suggest a dynamic process or acute phase reaction within the spinal cord and brainstem resulting from the exaggerated immune response as noted in tuberculoid-and BT-type leprosy. In fact, to support this hypothesis, both of our patients with brainstem lesions had type 1 lepra reaction at the time of MRI.…”
Section: Discussionmentioning
confidence: 59%
“…Traumatic BPIs are most commonly secondary to high-energy trauma, especially motor vehicle accidents and, less commonly, secondary to falls, bullet injuries, and penetrating injuries with a sharp object. Suggested mechanisms of the injury are traction, avulsion, laceration, compression, and contusion 6,11) . In this study, the major etiology was motor vehicle accidents.…”
Section: Discussionmentioning
confidence: 99%